Pengembangan Perangkat Pembelajaran Berbasis Mind Map melalui Google Clasroom pada Mata Pelajaran Elektronika dan Mikroprosesor di SMK Telkom Makassar - Andi Yasir Amsal; Hartini Ramli; Wakhid Yunendar (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Negeri Balikpapan., 2023)
This study is a research development, which aims at discovering: a) the learning conditions of Electronics and Microprocessor subject at SMK Telkom Makassar before applying it, b) the process of developing Mind Map-based learning tools through Google classroom in Electronics and Microprocessors subject, c) the results of the development of Mind Map-based learning tools through Google classroom in Electronics and Microprocessors subject, d) whether the Mind Map-based learning tools through Google classroom that have been developed are valid, practical, and effective being used in Electronics and Microprocessors subject at SMK Telkom Makassar. The development model used in this study was a modified development model by Borg & Gall. The steps in developing the learning tools consisted of 5 stages namely, (1) initial research and information gathering; (2) planning; (3) developing the initial product format; (4) product revisions; (5) field trials. The results of the study are: a) the observation result before the research being conducted, the researcher discovered that not all students have good response during the learning process, b) the learning tool developed had been validated by two experts with revision so that it is feasible to be used. The trials were conducted three times, namely one to one trial, small group trial, and large group trial, c) the products being produced are in the forms of learning tools consisted of syllabi, lesson plans, teaching materials, LKPD, media and learning assessment instruments, d) the results of the study show that learning using Mind Map-based learning tools through google classroom is stated as valid, practical, and effective with an average percentage of validity criteria namely media validation 96.87%, teaching material validation 91.04%, RPP validation 86.95%, LKPD validation 83.63%, practicality criteria shows students’ response 90.24%, teacher’s response 93.45%, and effectiveness criteria that 100% implementation is in very effective category.